Islamic societies to the nineteenth century - Lapidus, Ira Marvin, 1937- (New York)
xxxv, 758 s.
Keywords: "First published in 1988, Ira Lapidus' A History of Islamic Societies has become a classic in the field, enlightening students, scholars, and others with a thirst for knowledge about one of the world's great civilizations. This book, based on fully revised and updated parts one and two of this monumental work,describes the transformations of Islamic societies from their beginning in the seventh century, through their diffusion across the globe, into the challenges of the nineteenth century. The story focuses on the organization of families and tribes, religious groups and states, showing how they were transformed by their interactions with other religious and political communities. The book concludes with the European commercial and imperial interventions that initiated a new set of transformations in the Islamic world, and the onset of the modern era. Organized in narrative sections for the history of each major region, with innovative, analytic summary introductions and conclusions, this book is a unique endeavour." --